Transport, transformation, and ecological impacts of brominated flame retardants in soils: A comprehensive review - Jia Zhang; Dan Li; Ying Yuan; Kunlong Hui; Wenbing Tan (Environmental Chemistry and Ecotoxicology)
Brominated flame retardants (BFRs) have become significant contaminants of emerging concern (CECs), resulting in detrimental effects on soil health, human health, and ecosystem sustainability. Their environmental impacts have spurred extensive research into environmental chemistry and ecotoxicology. Despite the widespread detection of both BFRs and Novel Brominated Flame Retardants (NBFRs) in soils, there are few assessments of the environmental behavior and fate of the BFRs. Therefore, this review comprehensively identifies the sources, distribution, transport, transformation, ecotoxicological effects, and remediation strategies of BFRs in soils. Principal findings indicate that adsorption-desorption, mostly influenced by soil organic matter, controls the mobility and transformation of BFRs. Photolysis dominates surface soils, while aerobic and anaerobic biodegradation predominate in subsurface layers. The main factors influencing the bioavailability of BFRs are shed light on in this review. These factors such as the physicochemical properties of BFRs, soil characteristics, and combined pollution are specifically discussed. Moreover, the development, physiological, and biochemical responses of soil organisms to exposure to the BFRs are summarized. Single strategies for addressing BFRs have certain limitations. Urgent actions are needed to focus on environmental behavior and remediation strategies under the “One Health” framework to enrich research gap areas of BFRs, NBFRs, and transformation products.